Heat-conducting insulating enameled copper flat wire and preparation method thereof

By doping graphene oxide and alumina in the polyimide resin and grafting polyethylene glycol polymer on the surface, the problem of poor thermal conductivity of the enameled wire of the polyimide material is solved, achieving higher thermal conductivity and insulation properties, and extending service life.

CN119517518AActive Publication Date: 2025-02-25ZHEJIANG SANHANG ELECTRIC TECH CO LTD

Patent Information

Application Number
CN202411476781.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-25
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The thermal conductivity of polyimide enameled wires is poor, resulting in a shorter service life.

Method used

By doping graphene oxide in the polyimide resin and compounding with aluminum oxide, the polyethylene glycol polymer is further grafted by an epoxy silane coupling agent to form an insulating layer to reduce the conductivity of graphene oxide.

Benefits of technology

It significantly improves the thermal conductivity and insulation properties of the enameled wire and extends the service life of the enameled wire.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005096326180000141
    Figure BDA0005096326180000141
Patent Text Reader

Abstract

The invention belongs to the technical field of enameled wire new materials, and discloses a heat-conducting insulating enameled copper flat wire and a preparation method thereof. Comprising the following steps: 1) preparing graphene-aluminum oxide composite particles; the preparation method comprises the following steps of (1) preparing graphene-aluminum oxide composite particles, (2) uniformly mixing the graphene-aluminum oxide composite particles and a polyimide resin solution to obtain mixed paint, and (3) carrying out vacuum defoaming on the mixed paint, then coating the surface of the copper flat wire with the mixed paint, and carrying out thermocuring treatment to obtain the heat-conducting insulating enameled copper flat wire which has good heat-conducting property, so that the service life of the enameled wire is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of enameled wire materials, and in particular to a thermally conductive insulating enameled copper flat wire and a preparation method thereof. Background Art

[0002] Enameled wire is the main raw material for motors, electrical appliances, household appliances and other products. In particular, the power industry has continued to grow rapidly in recent years. The rapid development of household appliances has brought a wider application field for enameled wire, and with it, higher requirements for enameled wire. Enameled wire is a main type of winding wire. It consists of two parts: conductor and insulation layer. The bare wire is annealed and softened, and then painted and baked many times. However, it is not easy to produce products that meet both standard requirements and customer requirements. It is affected by factors such as raw material quality, process parameters, production equipment, and environment. Therefore, the quality characteristics of various enameled wires are different, but they all have four major properties: mechanical properties, chemical properties, electrical properties, and thermal properties.

[0003] There are many types of enameled wires. One of the earliest varieties developed in the world is acetal enameled wire. Although the temperature resistance level of this enameled wire is low, it is widely used in oil-immersed transformers due to its excellent high-temperature hydrolysis resistance. Secondly, polyester enameled wire and polyurethane enameled wire were successfully developed by Germany. Polyurethane enameled wire was developed by Bayer in Germany in 1937. Due to its direct welding, high-frequency resistance and dyeability, it is widely used in electronics, electrical appliances and other fields. Subsequently, the requirements for the properties of enameled wires became higher and higher. Polyesterimide enameled wires improved heat resistance by modifying polyester with imide, further expanding the application range of enameled wires; subsequently, enameled wires prepared from various materials such as polyimide enameled wires, polyamide enameled wires, and composite coated enameled wires were improved in different ways, improving the performance of enameled wires in all aspects.

[0004] Chinese patent publication number CN104130700 discloses a flexible polyimide insulating varnish and its preparation method, including polyester imide, cresol-type phenolic resin, p-tert-butylphenol-type phenolic resin, silicone oil, amino resin, aromatic polyamide, butyl orthotitanate, and solvent. The enameled wire made by the invention has good paint film flexibility. After the enameled wire is extended by 25%, the paint film does not crack after winding with 1 times the conductor diameter. However, the current polyimide enameled wire has poor thermal conductivity, resulting in a shortened service life of the polyimide enameled wire. Summary of the invention

[0005] The purpose of the present invention is to solve the above technical problems and propose a thermally conductive insulating enameled copper flat wire and a preparation method thereof. The thermally conductive insulating enameled copper flat wire prepared by the present invention has good thermal conductivity, thereby extending the service life of the enameled wire.

[0006] The technical solution of the present invention is achieved in this way:

[0007] A method for preparing a thermally conductive insulating enameled copper flat wire comprises the following steps:

[0008] 1) Preparing graphene-alumina composite particles;

[0009] 2) mixing the graphene-alumina composite particles and the polyimide resin solution uniformly to obtain a mixed paint;

[0010] 3) The mixed paint is subjected to vacuum degassing, and then the mixed paint is coated on the surface of the copper flat wire and subjected to heat curing treatment to obtain the product.

[0011] Preferably, in step 3), the thickness of the mixed paint coated on the surface of the copper flat wire is controlled to be 20-40 um.

[0012] Preferably, in step 3), the heat curing treatment temperature is 160-180° C., and the heat curing treatment time is 4-8 hours.

[0013] Preferably, in step 1), the method for preparing graphene-alumina composite particles comprises the following steps:

[0014] 11) adding aluminum chloride hexahydrate into deionized water and stirring to dissolve to obtain an aluminum chloride aqueous solution;

[0015] 12) adding graphene oxide to an aqueous solution of aluminum chloride, stirring evenly, adding aqueous ammonia dropwise under stirring until the pH value of the solution reaches 9-10, standing for aging, filtering, washing and drying to obtain a graphene-alumina precursor;

[0016] 13) placing the graphene-alumina precursor in a muffle furnace for calcining to obtain a graphene-alumina intermediate;

[0017] 14) adding the graphene-alumina intermediate to the hydrolyzate of the epoxy silane coupling agent, heating and stirring to react, and obtaining coupling agent-modified graphene-alumina;

[0018] 15) adding the coupling agent-modified graphene-alumina into a polyethylene glycol aqueous solution, adding a potassium hydroxide catalyst, heating and stirring to react, filtering, separating, washing and drying to obtain graphene-alumina composite particles.

[0019] In the prior art, polyimide is usually used as the resin matrix component of wire enamel, but the thermal conductivity of polyimide materials is poor, and its thermal conductivity is usually below 0.2W / (m·K). In order to improve the thermal conductivity of polyimide wire enamel, the present invention dopes graphene oxide into polyimide resin, and uses the thermal conductivity of graphene oxide to improve the thermal conductivity of polyimide materials. However, a further problem encountered is that graphene oxide is a conductive material, and its doping into polyimide resin will reduce the insulation performance of wire enamel. The present invention team synergistically solves the above problems from two aspects: on the one hand, by compounding graphene oxide and aluminum oxide to prepare a composite material, aluminum oxide is an electrical insulator, and mixing it with graphene oxide can reduce the electrical conductivity of graphene oxide. At the same time, aluminum oxide has certain thermal conductivity and will not affect the thermal conductivity of the material. On the other hand, the present invention grafts a polyethylene glycol polymer on the surface of the graphene-alumina composite material through an epoxy silane coupling agent. Polyethylene glycol is a non-ionic water-soluble polymer with excellent insulation. When polyethylene glycol is grafted to the surface of graphene oxide, an insulating layer is formed on the surface of graphene oxide. This insulating layer can block the transmission of electrons, thereby reducing the conductivity of graphene oxide. In addition, after polyethylene glycol is grafted to graphene oxide, it will interfere with the electron transmission path between graphene oxide sheets. Since polyethylene glycol molecules are insulating, they can act as obstacles to electron transmission and increase the distance between electron jumps, thereby reducing the overall conductivity and improving the insulation of the wire enamel.

[0020] Preferably, in step 12), the mass ratio of aluminum chloride hexahydrate to graphene oxide is 1:2-6.

[0021] Preferably, the calcination temperature in step 13) is 400-500°C.

[0022] Preferably, the heating reaction temperature in step 15) is 100° C. and the reaction time is 2 h;

[0023] The mass ratio of the coupling agent modified graphene-alumina to polyethylene glycol is 1:0.2-0.7.

[0024] In the technical solution of the present invention, in order to make the polyethylene glycol polymer reduce the conductivity of graphene oxide and improve its insulation, a sufficient amount of polyethylene glycol polymer must be grafted on the surface of the graphene-alumina composite material, and the mass ratio of the coupling agent modified graphene-alumina to polyethylene glycol is determined to be less than 1:0.2 through experiments. However, it was unexpectedly found in the experiment that with the increase in the amount of polyethylene glycol polymer, that is, when the mass ratio of the coupling agent modified graphene-alumina to polyethylene glycol is less than 1:0.7, the thermal conductivity of the graphene oxide-alumina composite material decreases significantly. This may be because polyethylene glycol is an amorphous polymer with low thermal conductivity. When an excess of polyethylene glycol is grafted onto the surface of the graphene oxide-alumina composite material, an insulating layer will be formed on the surface of the graphene oxide-alumina composite material. This layer of polyethylene glycol molecules will act as phonon scattering centers, increase the boundary scattering of phonons, and thus reduce the thermal conductivity of the graphene oxide-alumina composite material. Therefore, in order to make the enameled copper flat wire paint have good thermal conductivity and insulation performance, the mass ratio of the coupling agent modified graphene-alumina to the polyethylene glycol is strictly controlled within the range of 1:0.2-0.7.

[0025] A thermally conductive insulating enameled copper rectangular wire is prepared by the above method.

[0026] The present invention has the following beneficial effects:

[0027] 1) By adding graphene oxide to the wire enamel, the thermal conductivity of graphene oxide is used to improve the thermal conductivity of the polyimide material and extend the service life of the enameled wire;

[0028] 2) The composite material is prepared by compounding graphene oxide with aluminum oxide. Aluminum oxide is an electrical insulator. Mixing it with graphene oxide can reduce the electrical conductivity of graphene oxide. At the same time, aluminum oxide has certain thermal conductivity and will not affect the thermal conductivity of the material.

[0029] 3) Polyethylene glycol polymer is grafted onto the surface of the graphene-alumina composite material through an epoxy silane coupling agent. Polyethylene glycol is a non-ionic water-soluble polymer with good insulation. When polyethylene glycol is grafted onto the surface of graphene oxide, an insulating layer is formed on the surface of graphene oxide. This insulating layer can block the transmission of electrons, thereby reducing the conductivity of graphene oxide. In addition, after polyethylene glycol is grafted onto graphene oxide, it will interfere with the electron transmission path between graphene oxide sheets. Since polyethylene glycol molecules are insulating, they can act as obstacles to electron transmission and increase the distance between electron jumps, thereby reducing the overall conductivity and improving the insulation of the wire enamel. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] A method for preparing a thermally conductive insulating enameled copper flat wire comprises the following steps:

[0033] 1) preparing graphene-alumina composite particles;

[0034] 2) cresol and anhydrous ethanol are mixed at a volume ratio of 2:1 to obtain a solvent, a polyimide resin with a solid content of 30% is added to the solvent at a mass ratio of 1:50, and the mixture is stirred and dissolved to obtain a polyimide resin solution; graphene-alumina composite particles are added to the polyimide resin solution at a mass volume ratio of 1 g / 100 mL, and the mixture is mixed evenly to obtain a mixed paint;

[0035] 3) The mixed paint is vacuum degassed, and then the mixed paint is coated on the surface of the copper flat wire. The thickness of the mixed paint coated on the surface of the copper flat wire is controlled to be 30um. The mixed paint is heat-cured at a temperature of 175°C and a heat-curing time of 7h to obtain the product.

[0036] The preparation method of graphene-alumina composite particles comprises the following steps: 11) adding 3g of aluminum chloride hexahydrate into 200mL of deionized water and stirring to dissolve to obtain an aluminum chloride aqueous solution; 12) adding graphene oxide to the aluminum chloride aqueous solution, wherein the mass ratio of aluminum chloride hexahydrate to graphene oxide is 1:5, stirring evenly, adding ammonia water dropwise under stirring until the pH value of the solution reaches 9.5, standing and aging for 24h, filtering, washing and drying to obtain a graphene-alumina precursor;

[0037] 13) placing the graphene-alumina precursor in a muffle furnace and calcining it at 450° C. for 3 h to obtain a graphene-alumina intermediate;

[0038] 14) 90 mL of ethanol was mixed with 10 mL of water, and then 2 g of epoxy silane coupling agent KH-560 was added, and the mixture was stirred and hydrolyzed to obtain an epoxy silane coupling agent hydrolyzate, and 5 g of graphene-alumina intermediate was added to the epoxy silane coupling agent hydrolyzate, and the mixture was heated to 60° C. and stirred for reaction for 3 h. After filtration, separation, washing and drying, coupling agent-modified graphene-alumina was obtained;

[0039] 15) 5 g of coupling agent-modified graphene-alumina was added to a 2.0 wt.% polyethylene glycol (molecular weight 8000) aqueous solution, the mass ratio of coupling agent-modified graphene-alumina to polyethylene glycol was 1:0.6, 0.2 g of potassium hydroxide catalyst was added, and the reaction was heated and stirred at a reaction temperature of 100 ° C. The reaction time was 2 h, and the graphene-alumina composite particles were obtained after filtration, separation, washing and drying.

[0040] Example 2

[0041] A method for preparing a thermally conductive insulating enameled copper flat wire comprises the following steps:

[0042] 1) Preparing graphene-alumina composite particles;

[0043] 2) cresol and anhydrous ethanol are mixed at a volume ratio of 2:1 to obtain a solvent, a polyimide resin with a solid content of 30% is added to the solvent at a mass ratio of 1:50, and the mixture is stirred and dissolved to obtain a polyimide resin solution; graphene-alumina composite particles are added to the polyimide resin solution at a mass volume ratio of 1 g / 100 mL, and the mixture is mixed evenly to obtain a mixed paint;

[0044] 3) The mixed paint is subjected to vacuum degassing, and then the mixed paint is coated on the surface of the copper flat wire, the thickness of the mixed paint coated on the surface of the copper flat wire is controlled to be 30um, and a heat curing treatment is performed, the heat curing treatment temperature is 170°C, and the heat curing treatment time is 5h, thereby obtaining the product.

[0045] The preparation method of graphene-alumina composite particles comprises the following steps: 11) adding 3g of aluminum chloride hexahydrate into 200mL of deionized water and stirring to dissolve to obtain an aluminum chloride aqueous solution; 12) adding graphene oxide to the aluminum chloride aqueous solution, wherein the mass ratio of aluminum chloride hexahydrate to graphene oxide is 1:3, stirring evenly, adding ammonia water dropwise under stirring until the pH value of the solution reaches 9.5, standing and aging for 24h, filtering, washing and drying to obtain a graphene-alumina precursor;

[0046] 13) placing the graphene-alumina precursor in a muffle furnace and calcining it at 450° C. for 3 h to obtain a graphene-alumina intermediate;

[0047] 14) 90 mL of ethanol was mixed with 10 mL of water, and then 2 g of epoxy silane coupling agent KH-560 was added, and the mixture was stirred and hydrolyzed to obtain an epoxy silane coupling agent hydrolyzate, and 5 g of graphene-alumina intermediate was added to the epoxy silane coupling agent hydrolyzate, and the mixture was heated to 60° C. and stirred for reaction for 3 h. After filtration, separation, washing and drying, coupling agent-modified graphene-alumina was obtained;

[0048] 15) 5 g of coupling agent-modified graphene-alumina was added to a 2.0 wt.% polyethylene glycol (molecular weight 8000) aqueous solution, the mass ratio of coupling agent-modified graphene-alumina to polyethylene glycol was 1:0.3, 0.2 g of potassium hydroxide catalyst was added, and the reaction was heated and stirred at a reaction temperature of 100 ° C. The reaction time was 2 h, and the graphene-alumina composite particles were obtained after filtration, separation, washing and drying.

[0049] Example 3

[0050] A method for preparing a thermally conductive insulating enameled copper flat wire comprises the following steps:

[0051] 1) Preparing graphene-alumina composite particles;

[0052] 2) cresol and anhydrous ethanol are mixed at a volume ratio of 2:1 to obtain a solvent, a polyimide resin with a solid content of 30% is added to the solvent at a mass ratio of 1:50, and the mixture is stirred and dissolved to obtain a polyimide resin solution; graphene-alumina composite particles are added to the polyimide resin solution at a mass volume ratio of 1 g / 100 mL, and the mixture is mixed evenly to obtain a mixed paint;

[0053] 3) The mixed paint is vacuum degassed, and then the mixed paint is coated on the surface of the copper flat wire. The thickness of the mixed paint coated on the surface of the copper flat wire is controlled to be 30um. The mixed paint is heat-cured at a temperature of 170°C and a heat-curing time of 6 hours.

[0054] The preparation method of graphene-alumina composite particles comprises the following steps: 11) adding 3g of aluminum chloride hexahydrate into 200mL of deionized water and stirring to dissolve to obtain an aluminum chloride aqueous solution; 12) adding graphene oxide to the aluminum chloride aqueous solution, wherein the mass ratio of aluminum chloride hexahydrate to graphene oxide is 1:4, stirring evenly, adding ammonia water dropwise under stirring until the pH value of the solution reaches 9.5, standing and aging for 24h, filtering, washing and drying to obtain a graphene-alumina precursor;

[0055] 13) placing the graphene-alumina precursor in a muffle furnace and calcining it at 450° C. for 3 h to obtain a graphene-alumina intermediate;

[0056] 14) 90 mL of ethanol was mixed with 10 mL of water, and then 2 g of epoxy silane coupling agent KH-560 was added, and the mixture was stirred and hydrolyzed to obtain an epoxy silane coupling agent hydrolyzate, and 5 g of graphene-alumina intermediate was added to the epoxy silane coupling agent hydrolyzate, and the mixture was heated to 60° C. and stirred for reaction for 3 h. After filtration, separation, washing and drying, coupling agent-modified graphene-alumina was obtained;

[0057] 15) 5 g of coupling agent-modified graphene-alumina was added to a 2.0 wt.% polyethylene glycol (molecular weight 8000) aqueous solution, the mass ratio of coupling agent-modified graphene-alumina to polyethylene glycol was 1:0.5, 0.2 g of potassium hydroxide catalyst was added, and the reaction was heated and stirred at a reaction temperature of 100 ° C. The reaction time was 2 h, and the graphene-alumina composite particles were obtained after filtration, separation, washing and drying.

[0058] Example 4

[0059] A method for preparing a thermally conductive insulating enameled copper flat wire comprises the following steps:

[0060] 1) preparing graphene-alumina composite particles;

[0061] 2) cresol and anhydrous ethanol are mixed at a volume ratio of 2:1 to obtain a solvent, a polyimide resin with a solid content of 30% is added to the solvent at a mass ratio of 1:50, and the mixture is stirred and dissolved to obtain a polyimide resin solution; graphene-alumina composite particles are added to the polyimide resin solution at a mass volume ratio of 1 g / 100 mL, and the mixture is mixed evenly to obtain a mixed paint;

[0062] 3) The mixed paint is subjected to vacuum degassing, and then the mixed paint is coated on the surface of the copper flat wire, the thickness of the mixed paint coated on the surface of the copper flat wire is controlled to be 40um, and a heat curing treatment is performed, the heat curing treatment temperature is 180°C, and the heat curing treatment time is 8h.

[0063] The preparation method of graphene-alumina composite particles comprises the following steps: 11) adding 3g of aluminum chloride hexahydrate into 200mL of deionized water and stirring to dissolve to obtain an aluminum chloride aqueous solution; 12) adding graphene oxide to the aluminum chloride aqueous solution, wherein the mass ratio of aluminum chloride hexahydrate to graphene oxide is 1:6, stirring evenly, adding ammonia water dropwise under stirring until the pH value of the solution reaches 10, standing and aging for 24h, filtering, washing and drying to obtain a graphene-alumina precursor;

[0064] 13) placing the graphene-alumina precursor in a muffle furnace and calcining it at 500° C. for 3 h to obtain a graphene-alumina intermediate;

[0065] 14) 90 mL of ethanol was mixed with 10 mL of water, and then 2 g of epoxy silane coupling agent KH-560 was added, and the mixture was stirred and hydrolyzed to obtain an epoxy silane coupling agent hydrolyzate, and 5 g of graphene-alumina intermediate was added to the epoxy silane coupling agent hydrolyzate, and the mixture was heated to 60° C. and stirred for reaction for 3 h. After filtration, separation, washing and drying, coupling agent-modified graphene-alumina was obtained;

[0066] 15) 5 g of coupling agent-modified graphene-alumina was added to a 2.0 wt.% polyethylene glycol (molecular weight 8000) aqueous solution, the mass ratio of coupling agent-modified graphene-alumina to polyethylene glycol was 1:0.7, 0.2 g of potassium hydroxide catalyst was added, and the reaction was heated and stirred at a reaction temperature of 100 ° C. The reaction time was 2 h, and the graphene-alumina composite particles were obtained after filtration, separation, washing and drying.

[0067] Example 5

[0068] A method for preparing a thermally conductive insulating enameled copper flat wire comprises the following steps:

[0069] 1) preparing graphene-alumina composite particles;

[0070] 2) cresol and anhydrous ethanol are mixed at a volume ratio of 2:1 to obtain a solvent, a polyimide resin with a solid content of 30% is added to the solvent at a mass ratio of 1:50, and the mixture is stirred and dissolved to obtain a polyimide resin solution; graphene-alumina composite particles are added to the polyimide resin solution at a mass volume ratio of 1 g / 100 mL, and the mixture is mixed evenly to obtain a mixed paint;

[0071] 3) The mixed paint is vacuum degassed, and then the mixed paint is coated on the surface of the copper flat wire. The thickness of the mixed paint coated on the surface of the copper flat wire is controlled to be 20um. The mixed paint is heat-cured at a temperature of 160°C and a heat-curing time of 4 hours to obtain the product.

[0072] The preparation method of graphene-alumina composite particles comprises the following steps: 11) adding 3g of aluminum chloride hexahydrate into 200mL of deionized water and stirring to dissolve to obtain an aluminum chloride aqueous solution; 12) adding graphene oxide to the aluminum chloride aqueous solution, wherein the mass ratio of aluminum chloride hexahydrate to graphene oxide is 1:2, stirring evenly, adding ammonia water dropwise under stirring until the pH value of the solution reaches 9, standing and aging for 24h, filtering, washing and drying to obtain a graphene-alumina precursor;

[0073] 13) placing the graphene-alumina precursor in a muffle furnace and calcining it at 400° C. for 3 h to obtain a graphene-alumina intermediate;

[0074] 14) 90 mL of ethanol was mixed with 10 mL of water, and then 2 g of epoxy silane coupling agent KH-560 was added, and the mixture was stirred and hydrolyzed to obtain an epoxy silane coupling agent hydrolyzate, and 5 g of graphene-alumina intermediate was added to the epoxy silane coupling agent hydrolyzate, and the mixture was heated to 60° C. and stirred for reaction for 3 h. After filtration, separation, washing and drying, coupling agent-modified graphene-alumina was obtained;

[0075] 15) 5 g of coupling agent-modified graphene-alumina was added to a 2.0 wt.% polyethylene glycol (molecular weight 8000) aqueous solution, the mass ratio of coupling agent-modified graphene-alumina to polyethylene glycol was 1:0.2, 0.2 g of potassium hydroxide catalyst was added, and the reaction was stirred under heating at a reaction temperature of 100 ° C. The reaction time was 2 h, and the graphene-alumina composite particles were obtained after filtration, separation, washing and drying.

[0076] Comparative Example 1

[0077] The difference between Comparative Example 1 and Example 1 is that:

[0078] During the preparation of the thermally conductive insulating enameled copper flat wire, no graphene-alumina composite particles were added to the polyimide resin, and the remaining operating steps were the same as those in Example 1.

[0079] Comparative Example 2

[0080] The difference between Comparative Example 2 and Example 1 is:

[0081] During the preparation of thermally conductive insulating enameled copper flat wire,

[0082] The graphene-alumina composite particles were replaced with graphene oxide, and the remaining operation steps were the same as those in Example 1.

[0083] Comparative Example 3

[0084] The difference between Comparative Example 3 and Example 1 is that:

[0085] In the preparation process of graphene-alumina composite particles, steps 14) and 15) are omitted.

[0086] The remaining steps are the same as those in Example 1.

[0087] Comparative Example 4

[0088] The difference between Comparative Example 4 and Example 1 is that:

[0089] In the process of preparing graphene-alumina composite particles, steps 11), 12) and 13) are omitted.

[0090] The graphene-alumina intermediate is replaced by graphene oxide; the remaining operating steps are the same as those in Example 1.

[0091] Comparative Example 5

[0092] The difference between Comparative Example 5 and Example 5 is:

[0093] The mass ratio of coupling agent modified graphene-alumina to polyethylene glycol is 1:0.1, and the remaining operating steps are the same as those in Example 5.

[0094] Comparative Example 6

[0095] The difference between Comparative Example 6 and Example 4 is that:

[0096] The mass ratio of coupling agent modified graphene-alumina to polyethylene glycol is 1:0.8, and the remaining operating steps are the same as those in Example 4.

[0097] Comparative Example 7

[0098] The difference between Comparative Example 6 and Example 4 is that:

[0099] The mass ratio of coupling agent modified graphene-alumina to polyethylene glycol is 1:0.9, and the remaining operating steps are the same as those in Example 4.

[0100] Comparative Example 8

[0101] The difference between Comparative Example 8 and Example 4 is that:

[0102] The mass ratio of coupling agent modified graphene-alumina to polyethylene glycol is 1:1, and the remaining operating steps are the same as those in Example 4.

[0103] Performance Testing

[0104] 1. Thermal conductivity test:

[0105] The mixed paint obtained in the embodiment and the comparative example was coated on a steel plate with a thickness of 50 μm, and then subjected to heat curing treatment at a temperature of 160° C. for 4 hours, and the paint film was removed. The thermal diffusion coefficient of the polyimide film was measured by a laser flash method using a thermal diffusion coefficient measuring instrument (model LFA447, NETZSCH, Germany), and the thermal conductivity was calculated by multiplying the thermal diffusion coefficient measurement value by the density and specific heat.

[0106] 2. Insulation performance test:

[0107] The surface resistance of the paint film was measured using a YH-8200 digital insulation resistance tester with a test voltage of 100V. The higher the surface resistance of the paint film, the better the insulation performance of the paint film.

[0108]

[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a thermally conductive insulating enameled copper rectangular wire, characterized in that: The following steps are involved: 1) Preparation of graphene-alumina composite particles; 2) mixing the graphene-alumina composite particles and the polyimide resin solution uniformly to obtain a mixed paint; 3) The mixed paint is subjected to vacuum degassing, and then the mixed paint is coated on the surface of the copper flat wire and subjected to heat curing treatment to obtain the product.

2. The method for preparing a thermally conductive insulating enameled rectangular copper wire according to claim 1, characterized in that: In the step 3), the thickness of the mixed paint coated on the surface of the copper flat wire is controlled to be 20-40 um.

3. The method for preparing a thermally conductive insulating enameled rectangular copper wire according to claim 1, characterized in that: In the step 3), the heat curing treatment temperature is 160-180° C., and the heat curing treatment time is 4-8 hours.

4. The method for preparing a thermally conductive insulating enameled rectangular copper wire according to claim 1, characterized in that: In the step 1), the method for preparing graphene-alumina composite particles comprises the following steps: Add aluminum chloride hexahydrate into deionized water and stir to dissolve to obtain an aluminum chloride aqueous solution; Adding graphene oxide to an aqueous solution of aluminum chloride, stirring evenly, adding aqueous ammonia dropwise under stirring until the pH value of the solution reaches 9-10, standing for aging, filtering, washing and drying to obtain a graphene-alumina precursor; The graphene-alumina precursor is placed in a muffle furnace for calcination to obtain a graphene-alumina intermediate; The graphene-alumina intermediate is added to the hydrolyzate of the epoxy silane coupling agent, and the mixture is heated and stirred to react, thereby obtaining the coupling agent-modified graphene-alumina; The coupling agent-modified graphene-alumina is added into a polyethylene glycol aqueous solution, a potassium hydroxide catalyst is added, the mixture is heated and stirred for reaction, and the graphene-alumina composite particles are obtained through filtering, separation, washing and drying.

5. The method for preparing a thermally conductive insulating enameled rectangular copper wire according to claim 4, characterized in that: In the step 12), the mass ratio of aluminum chloride hexahydrate to graphene oxide is 1:2-6.

6. The method for preparing a thermally conductive insulating enameled rectangular copper wire according to claim 4, characterized in that: The calcination temperature in step 13) is 400-500°C.

7. The method for preparing a thermally conductive insulating enameled rectangular copper wire according to claim 4, characterized in that: In the step 15), the heating reaction temperature is 100° C. and the reaction time is 2 h; The mass ratio of the coupling agent modified graphene-alumina to polyethylene glycol is 1:0.2-0.

7.

8. A thermally conductive insulating enameled copper rectangular wire, characterized in that: The method is prepared by the method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Graphene-based heat-conduction composite material and preparation method thereof

    CN108102144A

  • Preparation method of enameled wire, and coil

    CN109599208A

  • Modified graphene reinforced epoxy resin composite material and preparation method thereof

    CN109897341A

  • Wire enamel material for enhancing heat dissipation based on graphene and preparation method of wire enamel material

    CN117659858A

  • Graphite-containing insulating flame-retardant composite plastic and preparation method thereof

    CN118755228A

Cited By

  • Lightweight injection molding part and preparation method thereof

    CN121021976A